Pengaruh Model Problem Based Learning Bermuatan SDGs Poin 13 pada Materi Perubahan Iklim terhadap Kemampuan Berpikir Kritis Peserta Didik - Afia Isnaini; Purwanti Widhy Hastuti (PT. Komunitas Peneliti Alinea, 2026)
21st-century skills are important in science learning, one of which is critical thinking skills. Therefore, this study aims to: (1) determine the differences in students' critical thinking skills between learning using the problem-based learning model containing SDGs 13 and the discovery learning model on climate change material and (2) determine the effect of the problem-based learning model containing SDGs 13 on students' critical thinking skills. This study is motivated by the low critical thinking skills of students. The novelty of this study is the integration of SDGs 13 into the problem-based learning model as a learning context that is relevant to students' lives to train critical thinking skills. This study is a quasi-experimental design with a pre-test post-test nonequivalent control group design. The research sample consisted of 30 students each from class VII D and class VII B of SMP Negeri 2 Berbah in the 2025/2026 academic year. Data analysis techniques include n-gain, normality, homogeneity, independent sample t-test, and effect size. The results of the study show that: (1) there is a significant difference in critical thinking skills between classes using the problem-based learning model containing SDGs 13 and classes using the discovery learning model on climate change material and (2) there is a strong influence of the problem-based learning model containing SDGs 13 on climate change material on students' critical thinking skills. In addition, indicate that students are able to analyze real problems and formulate solutions so as to support the development of 21st-century skills, especially critical thinking skills.